INFLUENCE OF AMINOGUANIDINE ON STATE OF NITRIC OXIDE’S SYSTEM AT EXPERIMENTAL LIVER CIRRHOSIS - Oleshchuk, O.M. (World of Medicine and Biology, 2014)
The influence of aminoguanidine (10 mg / kg i.p., 10 days) on nitric oxide system and morphological structure of the liver in experimental cirrhosis caused by prolonged administration CCl4. It was established that the development of cirrhotic liver injury, confirmed by the presence of morphologically pronounced sclerosis periportal fields and formation dysplastic regenerative nodules are accompanied by a decrease in the content of endothelial and increase inducible NO- synthase (iNOS), an increase in the concentration of stable nitric oxide metabolites nitrite anion levels in blood and a decrease in the liver. Activation indices of nitric oxide are accompanied by increased production of proinflammatory cytokines IL-1β, IL- 6 and TNF-α. The usage of selective iNOS inhibitor aminoguanidine in case of cirrhosis leads to reduction of nitrite anion and inducible NOS, both in blood and in liver and reduction of TNF-α in blood. Use of the drug does not lead to a significant improvement in the morphological state of the liver.